2020
DOI: 10.2147/ott.s259893
|View full text |Cite
|
Sign up to set email alerts
|

<p>Immune Checkpoint Inhibitor Therapy Achieved Complete Response for Drug-Sensitive<em> EGFR/ALK</em> Mutation-Negative Metastatic Pulmonary Large-Cell Neuroendocrine Carcinoma with High Tumor Mutation Burden: A Case Report</p>

Abstract: Large-cell neuroendocrine lung carcinoma (LCNELC) is classified into lung neuroendocrine tumors according to WHO 2015 classification guidelines and represents approximately 3% of all lung cancer. Because of the rarity of LCNELC, there is a lack of prospective studies guiding treatment. Here, we report a case of a patient with pT2aN2M0 stage IIIA LCNELC (drug-sensitive EGFR/ALK mutation-negative, PD-L1-negative but tumor mutation burden (TMB) high), who progressed rapidly after surgery but achieved a complete r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Indeed, on the basis of the studies discussed, genomic subtyping represents a valid tool to predict prognosis and detect the best treatment for each LCNEC patient (43). With regard to potential future opportunities, some cases are reported of patients treated with checkpoint inhibitors, often achieving radiological and clinical response, in particular after platinum-based first-line treatment failure (107)(108)(109)(110)(111). A few data are also available concerning targeted therapy, due to a low frequency of driver mutations in LCNEC patients, but mostly of them have reported a moderate efficacy of TKIs in this subset of disease (114,115,119,120).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, on the basis of the studies discussed, genomic subtyping represents a valid tool to predict prognosis and detect the best treatment for each LCNEC patient (43). With regard to potential future opportunities, some cases are reported of patients treated with checkpoint inhibitors, often achieving radiological and clinical response, in particular after platinum-based first-line treatment failure (107)(108)(109)(110)(111). A few data are also available concerning targeted therapy, due to a low frequency of driver mutations in LCNEC patients, but mostly of them have reported a moderate efficacy of TKIs in this subset of disease (114,115,119,120).…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the CR of pulmonary LCNEC to immune checkpoint inhibitors (ICI) is extremely rare, with only three case reports in the literature. [5][6][7] LCNEC is classified as pulmonary neuroendocrine carcinoma by the 2015 World Health Organization classification. The prognosis of pulmonary LCNEC is poor and standard therapy has not yet been established.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies showed that lung LCNEC has a quite specific pattern of programmed cell-death-protein-1-ligand-1 (PD-L1) expression, which is associated with prognosis. 21,22) Thus, immunotherapy may be a new strategy to manage LCNEC in the near future, although only a case report 23) and a small cohort NMC Case Report Journal Vol. 8, 2021 AWD: alive with disease, C: chemotherapy, DWD: dead with disease, LCNEC: large cell neuroendocrine carcinoma, ND: not described, NED: no evidence of disease (alive), R: radiation therapy, S: surgery.…”
Section: Discussionmentioning
confidence: 99%
“…For example, recent studies showed that lung LCNEC has a quite specific pattern of programmed cell-death-protein-1-ligand-1 (PD-L1) expression, which is associated with prognosis. 21 , 22) Thus, immunotherapy may be a new strategy to manage LCNEC in the near future, although only a case report 23) and a small cohort study 24) have been reported in lung. We need more studies from various standpoints to address sinonasal LCNEC.…”
Section: Discussionmentioning
confidence: 99%